Intralenticular changes in eyes with mature senile cataract on modified posterior segment optical coherence tomography - Pujari, Amar (Indian J Ophthalmol, 2020)
PURPOSE: To study the morphological changes within mature senile cataracts on modified posterior segment optical coherence tomography (OCT). METHODS: A cross-sectional observational study recruiting patients of mature cataracts admitted for elective cataract surgery in tertiary eye care. A modified OCT imaging of the lens was done and lenticular findings were noted by a single observer. Corresponding slit-lamp biomicroscopic findings and intraoperative experiences were also noted by a second observer and respective surgeons. RESULTS: Forty-four eyes of 44 patients were included. The mean age of patients was 65 ± 5.7 years. The intralenticular findings were uniform in groups of eyes, and they were characterized into three stages. First was a stage of early lamellar separation where small intralenticular clefts were noted superficially. Second was the stage of established lamellar separation where crescentic fluid clefts appeared interspersed between the lens fibers, and the depth increased as a function of severity. Both these stages did not show any distinct slit-lamp or intraoperative findings. A third stage of liquefaction identified as extensive lamellar separation with subcapsular fluid pockets. This was also reflected in slit-lamp biomicroscopy, showing the hydrated cortex with intraoperative challenges. Two cases showed peculiar changes, one of a hyperreflective subcapsular sheath and another of superficial nuclear lamellar separation. CONCLUSION: Mature cataracts may also show graded progression, which could be delineated on lenticular OCT. This could be of immense help in pre-operative planning and optimal management of these high-risk cases.